OPTIMALISASI PRODUKSI USAHATANI BUNCIS (Phaseolus vulgaris L.) DI KELURAHAN RAPAK KECAMATAN LOA JANAN ILIR KOTA SAMARINDA (Optimization of Bean Farming Production (Phaseolus vulgaris L.) in Rapak Dalam Urban Village, Loa Janan Ilir Subcity, Samarinda City) - MUTH MAINNAH; SITI BALKIS (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
Production must consider inputs usage in order to achieve optimal production and maximum revenue. The purposes of this study were to determine the optimal level of production and to know the maximum income of bean farming in Rapak Dalam Urban Village, Loa Janan Ilir Subcity, Samarinda City. The study was conducted from March to May 2018. The collected data in this research were primary and secondary data. Sampling was done by using census method with 33 respondents. Data analysis used quadratic and linier regresions. The results of this research show the average of bean production of 367.58 kg ha-1 cropping season (cs)-1, profit of IDR2,090,657.83 ha-1 cs-1,  the optimum production of 834.50 kg ha-1 cs-1, and  maximum income of IDR3,077,727.72 ha-1 cs-1. Bean farming in Rapak Dalam Urban Village has not reached the optimal production level and the income has not been maximum.